2018
DOI: 10.3390/f9020083
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Effects in Norway Spruce—European Beech Stands Are Modulated by Site Quality, Stand Age and Moisture Availability

Abstract: Abstract:Although mixing tree species is considered an efficient risk-reduction strategy in the face of climate change, the conditions where mixtures are more productive than monocultures are under ongoing debate. Generalizations have been difficult because of the variety of methods used and due to contradictory findings regarding the effects of the species investigated, mixing proportions, and many site and stand conditions. Using data from 960 plots of the Swiss National Forest Inventory data, we assessed wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
(97 reference statements)
3
5
0
Order By: Relevance
“…According to the estimates of our mixed model, the strongest effect, which explained most of the growth variation, was actually derived from the variation in DBH among trees and sites (note that size differences in our study are mainly due to age differences and not due to differences in canopy status). Our finding that mixing benefits increased with tree size in beech is in agreement with results of two recent studies, which reported increasing mixing benefits for beech with tree size/stand age in combination with spruce (Houpert et al, 2018) and pine (Forrester et al, 2017).…”
Section: Mixing Benefits For Both Species Increase With Tree Size Andsupporting
confidence: 93%
“…According to the estimates of our mixed model, the strongest effect, which explained most of the growth variation, was actually derived from the variation in DBH among trees and sites (note that size differences in our study are mainly due to age differences and not due to differences in canopy status). Our finding that mixing benefits increased with tree size in beech is in agreement with results of two recent studies, which reported increasing mixing benefits for beech with tree size/stand age in combination with spruce (Houpert et al, 2018) and pine (Forrester et al, 2017).…”
Section: Mixing Benefits For Both Species Increase With Tree Size Andsupporting
confidence: 93%
“…Maple, beech, spruce and oak showed the clear negative effect of mixtures with broadleaved trees (mixB), which is in accordance with the findings in Houpert et al [49]. Positive effects were found when the leading species was coniferous for larch and fir.…”
Section: Mixturesupporting
confidence: 90%
“…Positive effects were found when the leading species was coniferous for larch and fir. This is also supported by [49], although only the presence of coniferous trees was used rather than the proportion.…”
Section: Mixturementioning
confidence: 67%
“…Houpert et al [39] studied the influence of site quality, stand age and moisture availability in mixed Norway spruce-European beech stands and found out that Fagus sylvatica grew better in mixtures and this effect increased with site quality. A significant interaction between species proportions and stand age was found for both species: the older the stand, the better the growth of Fagus sylvatica and the lower the growth of Picea abies.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the influence of site quality on the complementarity effect, Pretzsch et al [38] carried out a research on mixed versus monospecific stands of Pinus sylvestris and Fagus sylvatica along a productivity gradient through Europe, covering an area where climatic variables took very different values, and did not find that overyielding was dependent on site quality or climate. On the other hand, other studies have pointed out that the interactions between species depend on a series of factors such as site quality, climate, stand age or stand density [22][23][24]39].…”
Section: Discussionmentioning
confidence: 99%